Control of the Nucleotide Cycle in Photoreceptor Cell Extracts by Retinal Degeneration Protein 3 - Wimberg, Hanna; Janssen-Bienhold, Ulrike; Koch, Karl-Wilhelm (Frontiers in Molecular Neuroscience, 2018)
Retinal degeneration protein 3 (RD3) is crucial for photoreceptor cell survival and linked to Leber Congenital Amaurosis type 12 (LCA12), a hereditary retinal disease in humans. RD3 inhibits photoreceptor guanylate cyclases GC-E and GC-F and is involved in transport of GCs from the inner to the outer segments. Otherwise, its role in photoreceptor physiology is poorly understood. Here, we describe a new function of RD3. Purified RD3 evoked an increase in guanylate kinase activity, an enzyme that is involved in the nucleotide cycle in photoreceptors. We demonstrate a direct interaction between guanylate kinase and RD3 using back-scattering interferometry and show by immunohistochemistry of mouse retina sections that RD3 and guanylate kinase co-localize in photoreceptor inner segments and to a lesser extent in the outer plexiform layer. Our findings point towards a more complex function of RD3 in photoreceptors. The RD3 – guanylate kinase interaction may also play a role in other cellular systems, while the GC – RD3 interaction is exclusive to photoreceptors.